Development of a Measure of Anti-Rape Attitudes as a Potential Protective Factor Against Rape Perpetration - Schapansky, Evelyn (Journal of interpersonal violence, 2025)
The role of attitudes toward women and sexual violence in predicting men’s perpetration of rape has been well documented in the literature. While research on rape perpetration has primarily focused on identifying risk factors, the limited understanding of protective factors has hindered the development of psychometric measures to assess attitudinal protective factors. However, comprehending these protective factors is essential for a comprehensive understanding of the risk of rape perpetration and the advancement of strength-based approaches. This research describes the development of a new scale designed to measure anti-rape attitudes (ARA) in young heterosexual men. To generate the initial item pool, relevant information was gathered from sexual violence support service websites and academic literature. This item pool underwent an external expert review for further item generation and cognitive interviews for content validation. This qualitative phase was followed by four quantitative studies for item reduction and scale validation. The resulting 19-item scale demonstrates good internal consistency (Cronbach’s α = .84). The ARA scale exhibits strong negative correlations with rape myth acceptance (RMA) and hostile sexism, and strong positive correlations with positive consent attitudes (PCA), supporting the scale’s construct validity. We further conducted hierarchical regression analyses to test the unique relationship of ARA with those constructs while controlling for RMA. These showed that ARA have significant, unique associations with PCA and ambivalent sexism. The development of this new scale enables a more comprehensive assessment of the risk of rape perpetration and opens up new avenues for research on protective factors against rape. Ultimately, this study constitutes an important step toward fostering strength-based approaches to combat sexual violence.